(untitled) (Atti del Sodalizio Glottologico Milanese, 2018)
Two Indo-Iranian names (probably Old Aryan) in regions under Mittani influence (14th BC), which are diverging, in form and/or semantics, from their contemporary comparanda in the IE languages of 2nd millennium Anatolian reflect different developments. The MN šat-ti-ú-a(z)-za /Šātiṷāza-/ (Nuza) : Ved. *sāti-vā́ja- (cf. Ved. vā́ja-sāti- ‘winning of the price’), has a first member /Šāti°/, which reflects the inherited sense of Ved. sani / sā ‘reach, win’ (*senh2-: Hom. ἀνύω ‘id.’, also ‘to finish, fulfill’, also, with secondary lexicalization, Hitt. šanḫu- ‘to roast’). Contrarily, Hitt. šan(a)ḫ- ‘seek, try’ reflects the lexicalization of the conative realisation of the aspectual prs. *sn̥-n-h2- of PIE *senh2-, which was inherited with its full paradigm, and previous to the separation of Anatolian and Core Indo-European. The MN in-tar-ú-da, en-dar-ú-ta /Indraūta-/ (letters of Amarna) : Ved. indrotá- ‘helped by ’, with °ūtá- , reflects the sense of Ved. avi / ū ‘to help, assist’ (*h2eu̯h1-: Lat. i-uuō, -āre ‘id.’, cf. ppp. °i-ūtus). Contrarily, the reflexes of *h2eu̯h1- in Hittite and Luvian (also in Lycian) mean ‘to run’, not ‘to help’ (cf. Hitt. LÚḫui̯ant- ‘fugitive’ [*‘runner’] vs. Ved. ávant- ‘helping, helper’, Lat. (ad)iuuans ‘id.’: *h2eu̯h1-ent-): this suggests that Anatolian has preserved the inherited PIE semantics *h2eu̯h1- and that the shift to ‘help’ is an innovation of Core IE, not shared by Anatolian. KEYWORDS: Proto-Indo-European, Indo-Iranian, Anatolian languages, reconstruction, lexicon